Original Sources and State of Research in the Development of Higher Engineering and Technical Education in Ukraine (the Second Half of the 19th - Early 20th Centuries) - Fedosova, Iryna (Pedagogical Discourse, 2013)
The historio-graphical review of original sources was made on the basis of analysis and the state of the development of higher engineering and technical education in Ukraine in the second half of the 19th – early 20th century was described. Different aspects of higher engineering and technical schools’ function were described in the works of researchers. There were the history of organization, the position of students and the university staff; teaching technical knowledge and general subjects; specificity of activity (students’ age, duties, examinations, school location, the purpose of lectures, optional courses, workshops, individual work etc.); the essence, purpose and objectives of working departments; views on comparison of the role and place of colleges in providing technical education; the role of technical institutions in the development of domestic production; the problem of engineering personnel training; the improvement of the system of higher education establishments management; the reforming of higher technical education system.